Mass and energy balancing : calculations for plant design - Pritchard, David; Feroz, Shaik (NewYork: CRC, 2021)
"The text provides a comprehensive set of calculations relating to mass and energy balances for an entire process plant. An ammonia synthesis plant is taken as a calculation model to develop the relevant mass and energy balances necessary for the design and subsequent production. Instead of teaching the basics, the text gives a detailed series of process integrated and illustrated calculations to help readers develop and design a process plant. This book will serve undergraduate Chemical Engineering students as a teaching aid in capstone design and related courses and gives useful insights to advanced students, researchers, and industry personnel within the Chemical Engineering field"--
Includes bibliographical references and index.
Keywords: Chemical process control; Chemical plants; Heat transfer; Mass transfer; Engineering mathematics -- Formulae